KREATIVITAS UDJO NGALAGENA : STUDI KEBERHASILAN PENGEMBANGAN KREATIVITAS DI SAUNG ANGKLUNG UDJO (SAU) - M, Budiman Mahmud (Jurnal Vokasi Indonesia, 2015)
This article is the result of qualitative research which focused on creativity, especially creativity Udjo Ngalagena in terms of personal, press, processes and products. The results showed that the various potentials and support from the family, community and school (education) makes Udjo being personally creative. Personal creative and press factor gives strength to Udjo Ngalagena to continue and develop their creativity amid the challenges and conditions of the times. Udjo Ngalagena succeeded in making angklung tradition into creative products in educational activities, production and performances regularly and formally at Saung Angklung Udjo (SAU) with reference to the traditional values of Sunda. The existence and development of the SAU in Bandung, West Java for almost a 50 years proves that Udjo Ngalagena succeeded in creating generations of creative and successfully strengthen the local cultural existence